2016
DOI: 10.1016/j.artd.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Still no single gold standard for using cementless femoral stems routinely in total hip arthroplasty

Abstract: BackgroundThere is now a clear trend with increased usage of cementless femoral stems for all ages and most patients. As the number of total hip arthroplasties (THAs) performed annually continues to increase with expanding indications for THA and demands for improved quality of life, so will the prevalence of THA in the elderly and aging populations. This is worrisome as the risk of complications with cementless femoral stems increases in elderly patients and those with poor bone quality. The purpose of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…The use of press-fit cementless femoral implants has increased substantially over the past decades and currently has become the mainstream in primary THA [10,11]. Recent studies showed that the initial fixation and long-term stability of the components were determinants that affect implant survivorship [12,13] and periprosthetic bone remodeling, which encompasses bone resorption as well as increase in bone density as a result of stress shielding or stress concentration, is associated with the long-term fixation of cementless implants [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The use of press-fit cementless femoral implants has increased substantially over the past decades and currently has become the mainstream in primary THA [10,11]. Recent studies showed that the initial fixation and long-term stability of the components were determinants that affect implant survivorship [12,13] and periprosthetic bone remodeling, which encompasses bone resorption as well as increase in bone density as a result of stress shielding or stress concentration, is associated with the long-term fixation of cementless implants [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis of implant combinations 48 found no association between implant system and risk of revision, although other studies have mixed conclusions. 4954 These studies relied on structured records of revision and registry data, and thus are complemented by our analysis of real world evidence derived from EHRs. We also found that patients with structured records of revision surgery reported more hip pain in the post replacement, pre-revision period than patients who did not.…”
Section: Discussionmentioning
confidence: 99%
“…According to some researchers, a clear consensus on when to use cemented stems is missing (Moskal et al. 2016). This lack of consensus and data was one of the reasons to perform this study.…”
Section: Discussionmentioning
confidence: 99%
“…2014), studies set different thresholds for “older age” patients (Moskal et al. 2016), which affects the results depending on the study population. Since the definition of “elderly” is also unclear in the orthopedic literature (Sabharwal et al.…”
Section: Discussionmentioning
confidence: 99%